THE EFFECT OF GLOBAL GEOPOLITICAL RISKS ON TRADE OPENNESS (Eureka Journal of Humanities and Social Research, 2026)
As global geopolitical risks continue to intensify, international trade openness is encountering severe challenges. This study utilizes panel data from multiple countries spanning 1985 to 2022 to systematically investigate the impact of geopolitical risks on national trade openness. The empirical results show that geopolitical risks significantly suppress trade openness, confirming the detrimental effects of geopolitical shocks on a country’s degree of external economic liber- alization. Furthermore, greater fiscal freedom and sound fiscal conditions are found to effectively alleviate this negative impact, highlighting the role of robust fiscal institutions in enhancing national resilience to external shocks. Heterogeneity analysis reveals that the negative effect is more pronounced in countries with lower government integrity and weaker monetary freedom. To mitigate the institutional instability brought about by geopolitical shocks, this paper suggests strengthening fiscal governance, reinforcing financial market mechanisms, improving the quality of government governance, and enhancing regional cooperation to build collective risk man- agement capacity, thereby promoting the long-term and sustainable development of global trade openness.
Keywords: Geopolitical risks Trade openness Fiscal freedom Fiscal health